2015
DOI: 10.1161/hypertensionaha.114.04540
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exertion Elicits a H 2 O 2 -Dependent Vasodilator Mechanism in the Microvasculature of Exercise-Trained but Not Sedentary Adults

Abstract: Brachial artery flow mediated vasodilation in exercise trained (ET) individuals is maintained after a single bout of heavy resistance exercise compared to sedentary (SED) individuals. The purpose of this study was to determine if vasodilation is also maintained in the microcirculation of ET individuals. A total of 51 SED and ET individuals underwent gluteal subcutaneous fat biopsy before and after performing a single bout of leg press exercise. Adipose arterioles were cannulated in an organ bath and vasodilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 24 publications
(37 reference statements)
5
80
1
Order By: Relevance
“…7 But for couch potatoes, a smaller jump in blood pressure during weight lifting impaired endothelial function, reducing NO-mediated dilation. 8 The results were similar in cell culture: microvessels from nonathletes switch from NO to hydrogen peroxide release when pressure increases, mimicking the results for patients with cardiovascular disease. 9 Now, Gutterman and others are working to understand how routine exercise in athletes protects blood vessel function from the deleterious effects of stress.…”
supporting
confidence: 56%
“…7 But for couch potatoes, a smaller jump in blood pressure during weight lifting impaired endothelial function, reducing NO-mediated dilation. 8 The results were similar in cell culture: microvessels from nonathletes switch from NO to hydrogen peroxide release when pressure increases, mimicking the results for patients with cardiovascular disease. 9 Now, Gutterman and others are working to understand how routine exercise in athletes protects blood vessel function from the deleterious effects of stress.…”
supporting
confidence: 56%
“…Isolated microvessels (ex vivo) have been used to demonstrate that acute strenuous physical exertion reduces endothelium-dependent vasodilator function in the microcirculation as well [11,12]. Adequate perfusion in the microcirculation is essential for organ and tissue health.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired microvessel function has been linked to hypertension, obesity, and type 2 diabetes mellitus [13]. Proposed mediators of acute physical exertion-induced arterial dysfunction include transient exposure to hypertension, increased sympathetic nervous activity, and activation of renin-angiotensin-aldosterone system [9,11,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 This was confirmed by two studies showing that in rat-isolated coronary arterioles 24 and mesenteric arteries, 22 cellular deformation induced by pressure, stretch and wall shear stress, potentiated the release of NO resulting in dilation, despite an increase in ROS production. However, Gutterman's group recently reported that in pressurized human peripheral arterioles, a severe increase in intravascular pressure for 30 min induced either ex vivo (in static conditions) 25 or in vivo (in pulsatile conditions), 26 promoted endothelial dysfunction evidenced by reduced eNOS-dependent NO activity and excessive ROS production. Therefore, both a lack of pulsatile pressure and its excess are damaging to the endothelium as they both impair NO-dependent dilations.…”
Section: Introductionmentioning
confidence: 99%